Traveller BehavÄ±oral Changes: Push And Pull Factors AnalysÄ±s - Octaviany, Vany; Ervina, Ersy (APMBA (Asia Pacific Management and Business Application), 2023)
During COVID-19, there has been a change in traveler behavior. Each age group has particular travel preferences and interests, but few studies have examined the changes in the need and desires of travelers' activities. This study aims to identify profiles based on traveler demographics and analyze changes in traveler behavior based on motivation in the form of push and pull factors during an outbreak in Bandung Regency. This study uses a quantitative descriptive method by distributing online questionnaires to 257 tourists. The results describe the demographics of travelers (millennials, middle-aged, and old age), consisting of the area of origin, occupation, gender, education, and income of tourists. The analysis of motivational aspects of push and pull factors shows that millennials and people of middle age still have the same preference, namely choosing destinations that are unique with natural views and relaxing activities that eliminate boredom. Meanwhile, among elderly tourists, there is a behavior change; where previously they preferred destinations related to crowds, such as shopping, city tours, or visiting historical places, they are now turning to natural tourism, intending to refresh themselves and improve their health.